2022
DOI: 10.1002/adfm.202202072
|View full text |Cite
|
Sign up to set email alerts
|

Two Birds with One Stone: Contemporaneously Boosting OER Activity and Kinetics for Layered Double Hydroxide Inspired by Photosystem II

Abstract: The poor catalytic kinetics together with unsatisfied activity of nonprecious metal electrocatalysts for oxygen evolution reaction hamper their applications in industrial water electrolysis. Inspired by the oxygen evolution cluster of photosystem II in nature, Li + -doped NiFe layered double hydroxide modified with carboxylate is constructed by in situ growth on Ni foam (NFCL(70)-LDH @ NF) via one-pot redox synthesis. Herein, lithium acetate is introduced to regulate the electronic structure and improve proton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…As shown in Figure S2, the diffraction peaks are indexed to standard Ni(OH) 2 (PDF# 38-0715), being consistent with LDH. 21 Scarce difference in XRD patterns indicates that the phase composition are well maintained after the introduction of ligand. The high-resolution transmission electron microscopy (HR-TEM) images are further carried out to detect structure information.…”
Section: Designing and Characterizationsmentioning
confidence: 99%
“…As shown in Figure S2, the diffraction peaks are indexed to standard Ni(OH) 2 (PDF# 38-0715), being consistent with LDH. 21 Scarce difference in XRD patterns indicates that the phase composition are well maintained after the introduction of ligand. The high-resolution transmission electron microscopy (HR-TEM) images are further carried out to detect structure information.…”
Section: Designing and Characterizationsmentioning
confidence: 99%
“…11,12 As a result, developing costeffective electrocatalysts from earth-abundant metals plays an essential role in robust and efficient OER electrocatalysts. 13 Currently, a variety of transition metal (Fe, Co, Ni and Cu)based nanomaterials (alloys, 14,15 oxides, 16 hydroxides, [17][18][19] sulfides, 20,21 phosphides, [22][23][24] and nitrides 25,26 ) have been reported as extraordinarily promising noble-metal-substitute OER catalysts under alkaline conditions. Thereinto, FeNibased materials, especially the FeNi hydroxides, have shown excellent OER electrocatalytic activity in alkaline media.…”
Section: Introductionmentioning
confidence: 99%
“…11 For example, Lu et al decorated Li + -doped NiFe LDH on a Ni foam [NFCL(70)-LDH@NF] and found that it exhibited excellent OER performance over a month under the simulated industrial condition. 12 Regrettably, less-exposure active sites and poor electron conductivity tremendously limited its OER performance, necessitating further development. Transition-metal chalcogenides such as NiS, 13 Ni 3 S 2 , 14 MoS 2 , 15 and CoS 16 have attracted widespread attention because of their tunable chemical composition and costeffectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, transition-metal-based layered double hydroxide (LDH) exhibits broad application prospects, which contains hydroxide ions as well as divalent and trivalent metal cation layers and is considered as the most promising catalyst materials for electrocatalysis due to its unique two-dimensional (2D) structure, abundant interstratified channels, and rich layered structures . For example, Lu et al decorated Li + -doped NiFe LDH on a Ni foam [NFCL(70)-LDH@NF] and found that it exhibited excellent OER performance over a month under the simulated industrial condition . Regrettably, less-exposure active sites and poor electron conductivity tremendously limited its OER performance, necessitating further development.…”
Section: Introductionmentioning
confidence: 99%